Exact galactic disk-haloes model in Einstein-Maxwell gravity (2018)
An exact model in Einstein-Maxwell gravity describing a magnetized galactic disk-halo system is presented. The description of properties of the stationary metric and its source are discussed. All the expressions are presented in terms of an Harmonic function. A “generalization” of the Kuzmin potential is used as a particular example. The solution obtained is asymptotically Minkowskian in general and turns out to be singularity free. All the relevant quantities show a reasonable physical behavior. Copyright © 2018 by the Editors.All rights reserved.